A follow-up of the University of the Philippines External Studies Graduate Education Students, Paniqui Center, Tarlac - Olonan, Zenaida Aganan 1934- (s.n.], 1969)
The purpose of the study is to secure data and information on the personal characteristics, academic performance and changes in the educational and professional status of 112 students enrolled during the school year 1963-1964 at the University of the Philippines External Studies, Panique Center, Tarlac. This study is part of the effort to evaluate the educational leadership role of the University of the Philippines in providing a continuing education of school officials and teachers.